The Influence Of Independent Board Of Commissioners, Audit Committee, And Audit Quality On Tax Avoidance - Yuliana - Gunawan; Yunita - Christy; Se Tin - Se Tin; Livia - Jonathan (BALANCE: Economic, Business, Management and Accounting Journal, 2021)
ABSTRACT  This study is aimed to examine and analyze the influence of Independent Board of Commissioners, Audit Committee, and Audit Quality on Tax Avoidance. The sample in this study is mining companies listing on the Indonesia Stock Exchange in the period 2017-2019. Researchers are interested in doing this study because the mining sector provides high economic value to the country but the tax contribution from this sector is still minimal. The analysis used the multiple linear regression technique using the SPSS 20.0 program. The results of this study indicate that partially independent board of commissioners and audit quality have an effect on tax avoidance, however the audit committee has no partial effect on tax avoidance. Simultaneously the independent board of commissioners, audit committee and audir quality have an effect on tax avoidance. This study is expected to provide benefits for the government, companies and for future researchers.Keywords                    : Independent Board of Commissioners; Audit Committee; Audit                                        Quality;Tax AvoidanceCorrespondence to        : yuliana_ok99@yahoo.com ABSTRAK  Studi ini bertujuan untuk memverifikasi dan menganalisis pengaruh Dewan Komisaris Independen, Komite Audit, dan Kualitas Audit terhadap Penghindaran Pajak. Pengambilan contoh dalam penelitian ini adalah perusahaan yang bergerak dibidang pengambilan sumber daya alam/pertambangan yang listing di Bursa Efek Indonesia periode 2017-2019. Peneliti tertarik melakukan penelitian ini karena sektor pertambangan memberikan nilai ekonomi yang tinggi bagi negara namun kontribusi pajak dari sektor tersebut masih minim. Teknik penguraian data yang digunakan adalah regresi linier berganda dengan menggunakan program SPSS 20.0. Hasil dari studi ini menunjukkan bahwa secara parsial Dewan Komisaris Independen dan Kualitas Auditr berpengaruh terhadap Penghindaran Pajak, sedangkan Komite Audit tidak berpengaruh terhadap Penghindaran Pajak. Secara simultan Dewan Komisaris Independen, Komite Audit dan Kualitas Audit berpengaruh terhadap Penghindaran Pajak. Studi ini diharapkan dapat memberikan kontribusi bagi perusahaan dan peneliti selanjutnya.Kata kunci                  : Dewan Komisaris Independen; Komite Audit; Kualitas Audit;   Penghindaran Pajak